Botox to reduce drooling in South African neurologically impaired children : a retrospective study. - Hay, Nicola Michelle (My University, 2009)
Drooling management in the neurologically impaired pediatric population is a challenge. Surgery is considered an invasive procedure, while behaviour modification techniques, correction of situational factors and oral-motor therapy do not always produce sustained improvement. In recent years Botox® has been investigated. This study comprised analyses of clinical data obtained from a Drooling Treatment Project (DTP) conducted at a school for special needs children in South Africa. The aims of the DTP were to establish the response of drooling in a number of different contexts, following bilateral submandibular salivary gland injections of Botox®. Two groups of children were involved, 7 children with cerebral palsy and 2 children with operculum syndrome. Drooling was assessed in 5 different situations and at different time points pre- and post Botox® injection up to 6 months. Parents’/primary caregivers’ perceptions of drooling and treatment with Botox® were also measured using an interview form and a quality of life questionnaire. Results showed that drooling was reduced in all situations, with significant reductions in the general and communicating situations. These results indicate that the context in which drooling occurs is an important factor and suggest the value of considering the situational context when making drooling judgements. Further, there was a difference in the pattern of response between the 2 groups. This finding has implications, not only for future research, but also for models of explanation of the effects of Botox®. Most parents/primary caregivers felt their children’s lives and their own had improved following the Botox® injection and would repeat the treatment. Clinical and research implications are discussed, with reference to the South African context.
Keywords: Cerebral palsy; Operculum syndrome; Drooling; Salivary glands; Botulinum toxin type A; Quality of life; Severity and frequency rating scales; Botox